2019
DOI: 10.12691/wjce-7-4-2
|View full text |Cite
|
Sign up to set email alerts
|

An Undergraduate Experiment Using Cyclodextrin – Assisted Sensitive Fluorescence Detection and Quantitation of Dapsone Drug in Wastewater Samples

Abstract: The guest-host interaction between Dapsone drug and β-cyclodextrin (β-CD) was investigated using fluorescence spectroscopy, 1 H-NMR, and liquid chromatography with fluorescence detection. The optimized conditions for the interaction were investigated by spectrofluorometry and were found to be at 0.2 mg/mL (0.176 mM) of β-CD and pH 8.8. For these conditions, very low concentration of Dapsone drug of 2.4 ng/mL (12.97 nM) can be detected. The standard addition method was utilized to detect Dapsone in influent and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Wastewater samples were analyzed for naproxen drug using an automated extraction equipment from Horizon Technology SPE-DEX 4790, (Salem, United States), using previously reported extraction steps ( Meetani et al, 2019 ; Maraqa et al, 2020 ). The Atlantic ® HLB-M disks with N-vinylpyrrolidone and divinylbenzene sorbents were used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wastewater samples were analyzed for naproxen drug using an automated extraction equipment from Horizon Technology SPE-DEX 4790, (Salem, United States), using previously reported extraction steps ( Meetani et al, 2019 ; Maraqa et al, 2020 ). The Atlantic ® HLB-M disks with N-vinylpyrrolidone and divinylbenzene sorbents were used.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, HPLC with fluorescence detection in the presence of β-cyclodexrin was used for the sensitive detection and quantitation of several drugs in complex matrices ( Meetani et al, 2019 ; Alremeithi et al, 2016 ; Saleh et al, 2014 ; Saleh et al, 2011 ). For instance, Alremaithi et al have reported the determination of p-amino hipparic acid in urine samples using HPLC- FLD; β-cyclodexrin was used as a mobile phase additive to enhance the biomarker fluorescence detection through supramolecular interaction ( Alremeithi et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%